Alginate Oligosaccharide Coordinately Modulates Endogenous Phytohormone Profiles to Enhance Tomato Growth - Yun Li; Jianxia Wang; Kai Fan; Lingru Guo; Leiping Hou; Yanxiu Miao; Meihua Sun; Yaling Li; Longqiang Bai (Horticulturae)
Alginate oligosaccharides (AOSs) have been shown to be effective in enhancing crop growth. However, their functions in horticulture crops and growth-promoting mechanisms remain insufficiently characterized. This study employed pot cultivation experiments to investigate the effects of AOS root drenching (0, 15, 30, 45 mg·L−1) on tomato (Solanum lycopersicum L.) seedling growth, photosynthetic performance, and phytohormone accumulation. The results showed that AOS promoted the leaf count per plant, leaf area of the youngest fully expanded leaves, shoot and root dry mass, chloroplast pigment contents and photosynthetic rate of tomato seedlings. And the 30 mg·L−1 treatment consistently showed optimal efficacy, in which tomato seedlings also exhibited a significantly longer total root length, a larger root surface area and a greater number of root tips compared to the control. Phytohormone profiling revealed that AOS differentially regulated shoot/root phytohormones as follows: increasing auxins/cytokinins (CKs)/GA19 content in shoots and Indole-3-acetic acid (IAA)/CKs/1-aminocyclopropane-1-carboxylic acid (ACC) content in roots, while decreasing root Jasmonic acid (JA)/5-deoxystrigol (5DS) contents. Finally, these findings demonstrate that AOS enhances tomato growth by coordinately reprogramming phytohormone homeostasis.